Respuesta :

irspow

Answer:

Step-by-step explanation:

Since one equation has -4x and the other has 4x one can simply add the equations together to eliminate the variable x.

4x+8-4x-2y=-24-12

8-2y=-36 subtract 8 from each side

-2y=-44 divide each side by -2

y=22, and since 4x+8=-24

4x=-32 divide each side by 4

x=-8, so the solution is at the point

(-8,22)

Answer:

-4x - 2y = -12

4x + 8 = -24      typed incorrect should be 4x + 8y = -24

Step-by-step explanation:

add the two equations all like terms

-4x - 2y = -12

4x + 8y = -24

-4x + 4x = 0x

-2y + 8y = 6y

-12 + -24 = - 36

now reconstruct the equation

0x + 6y = -36

       6y = -36

        y  = -36/6             <----------------------   Final Answer is y = -6

Find x

-4x - 2y = -12

-4x = -12 +2y

-2x  = -6 + y                     divide both sides by -2

   x = (-6+y)/-2                 plug in -6 for y

   x = (-6 + -6) / -2

   x = -12 /-2

   x = 6    <----------------------   Final Answer is x = 6

checking answer for x=6 and y= -6

-4x - 2y = -12    -4(6) - 2(-6)      =     - 24 + 12   = -12        -12 = -12

4x + 8 = -24      4(6) + 8(-6)      =       24 + -48 = -24       -24 = -24